Erratum: Differences in Ribosome Binding and Sarcin/Ricin Loop Depurination by Shiga and Ricin Holotoxins. Toxins 2017, 9, 133 - Toxins Editorial Office (Toxins, 2018)
We wish to make the following correction to the published paper [1].[...]